Mind–Body Exercises for Non-motor Symptoms of Patients With Parkinson’s Disease: A Systematic Review and Meta-Analysis - Wang, Kai; Li, Kunbin; Zhang, Peiming; Ge, Shuqi; Wen, Xiaopeng; Wu, Zhiyuan; Yao, Xianli; Jiao, Bing; Sun, Pingge; Lv, Peipei; Lu, Liming (Frontiers in Aging Neuroscience, 2021)
Abstract Objective: This study aimed to systematically evaluate the effects of mind-body exercise on global cognitive function, depression, sleep disorders, fatigue level and quality of life in a Parkinson’s disease (PD) population. Methods: Total six English and Chinese databases were searched for articles published up to May 2021. Randomized controlled trials (RCTs) evaluating mind-body excises on nonmotor symptoms of PD were included. The Cochrane Risk of Bias Tool was used to assess the methodological quality, and we defined high-quality studies as having a low risk of bias in four or more domains. Global cognitive function was considered the primary outcome and was assessed using the Montreal Cognitive Assessment (MOCA). The secondary outcomes included quality of life (QOL), fatigue, depression and sleep quality, which were measured using the Parkinson’s Disease Questionnaire (PDQ-39), 16-item Parkinson’s Disease Fatigue Scale (PFS-16), Beck Depression Inventory (BDI) and revised Parkinson’s Disease Sleep Scale (PDSS-2), respectively. Subgroup analyses were conducted for global cognitive function and QOL to assess the optimal treatment measure across the various mind-body exercises. Results: Fourteen randomized controlled trials with 404 patients were finally included in the meta-analysis. Eight (57.14%) studies were of high quality. The pooled results showed that mind-body exercises generally had a significant advantage over the control intervention in improving global cognitive function (MD= 1.68; p= 0.0008). The dose subgroup analysis revealed that the low dose (60–120 min per week) and moderate dose (120–200 min per week) significantly increased MoCA scores compared with the control group (MD= 2.11, P=0.01; MD= 1.27, P=0.02, respectively). The duration subgroup analysis indicated a significant difference in the effect of the duration (6–10 weeks, >15 weeks) on increasing MoCA scores compared with the control group (MD= 3.74, P<0.00001; MD= 1.45, P=0.01, respectively). Conclusions: Mind-body exercise may improve global cognitive function, sleep quality and quality of life in the PD population. In addition, low to moderate doses and appropriate durations significantly improved global cognitive function.